Catholic beliefs and traditions ancient and ever new - O'Grady, John F. (New York : Paulist Press, 2001)
A Roman Catholic priest explores the origins of many revered Catholic beliefs and traditions in this comprehensive volume. Contains discussion and study questions which may be used for either group discussion or personal reflection.
The problem of God -- Images of God -- Jesus--the revelation of God -- The Bible--record of God's revelation -- Images of the Early Church and the New Testament -- Pope, bishops and heirarchy -- The liturgy and the sacraments of the Church -- Mediation--Mary and the saints -- Prayer and devotion -- Original sin -- Grace in the Catholic tradition -- Death and eschatology -- Heaven, purgatory and hell -- Conscience in Catholic tradition -- Catholic morality -- Conclusion: American Catholics and Vatican II.
Includes bibliographical references (p. 335-347) and index.
Description based on print version record.
Keywords: Catholic Church -- Doctrines; Catholic Church -- Customs and practices; RELIGION / Christianity / Catholic; Electronic books